2020
DOI: 10.1177/0300060520918792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of unilateral testicular torsion at different ages on male fertility

Abstract: Objective To investigate the effect of early-life unilateral testicular torsion on adult male fertility. Methods Clinical information was collected for 122 patients who had experienced unilateral testicular torsion at a median age of 15.5 years. The recent pregnancy rate and time to pregnancy experienced by the patients’ female partners were assessed by structured interviews. Data were analyzed by the chi-squared test and Student’s t-test. Results Seventy-two patients with testicular torsion met the criteria f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…According to Mäkelä’s study, 42 children were born in relationships to 56% of men after an orchiectomy because of TT and as many as 81% of men who had a testicular detorsion. Zhang et al, 43 on the other hand, analysed the percentage of children born by comparing the type of operation in the case of testicular torsion (relationship: orchiectomy/detorsion) and the age at which the man was operated on. They stated that the most favourable dependence (93%/100%) was in cases of operations under 14 years old .…”
Section: Discussionmentioning
confidence: 99%
“…According to Mäkelä’s study, 42 children were born in relationships to 56% of men after an orchiectomy because of TT and as many as 81% of men who had a testicular detorsion. Zhang et al, 43 on the other hand, analysed the percentage of children born by comparing the type of operation in the case of testicular torsion (relationship: orchiectomy/detorsion) and the age at which the man was operated on. They stated that the most favourable dependence (93%/100%) was in cases of operations under 14 years old .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with TT in adulthood had lower pregnancy rates than those with TT in childhood. Patients treated with orchiectomy in adulthood had a significantly longer time to pregnancy in comparison with adults treated with orchidopexy [ 34 ]. A study investigating 63 patients with TT (41 orchidopexies and 22 orchiectomies) demonstrated no difference in pregnancy rates, and a slightly longer time to pregnancy in the orchiectomy group (90.2% vs. 90.9%; 6.6 +/− 5.50 vs. 7.2 +/− 5.4 months for orchidopexy vs. orchiectomy) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical repositioning/orchiopexy in adolescent torsion patients showed a significantly higher recent pregnancy rate among the three groups, based on age at the time of torsion, and shorter duration to pregnancy than orchiectomy patients. 17 Generally, it looks that some patients experience decreased sperm motility and reduced overall sperm counts at long-term follow-up after TT that perhaps making them subfertile. However, we need more highquality researches and available studies that are not limited by selection bias.…”
Section: Casementioning
confidence: 99%